2013
DOI: 10.3109/08977194.2013.840297
|View full text |Cite
|
Sign up to set email alerts
|

Cellular reprogramming into a brown adipose tissue-like phenotype by co-expression of HB-EGF and ADAM 12S

Abstract: Abnormal adipogenesis leads to excessive fat accumulation and several health disorders. Mouse fibroblasts (MLC) transfected with ADAM 12S and HB-EGF promoted lipid accumulation. Addition of KBR-7785, an ADAM 12S inhibitor, to HB-EGF/ADAM 12S expressing cells suppressed adipogenesis. BrdU incorporation was attenuated and enhanced mitotracker staining was observed in HB-EGF/ADAM 12S cells. Quantitative real time RT-PCR resulted in elevated levels of expression of three brown adipose tissue (BAT) genes (PRDM16, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Previous reports suggested that the HB-EGF is a central regulator for the stem cell proliferation and differentiation as recently reviewed by the Vinante et al [31]. Zhou et al reported that the HB-EGF is involved in the transdifferentiation of the fibroblasts to adipose tissue-like cells [32]. Lee et al reported that the recombinant HB-EGF is an inhibitor of the initial commitment of differentiation of pluripotent mesenchymal stem cells to the adipogenesis [33].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggested that the HB-EGF is a central regulator for the stem cell proliferation and differentiation as recently reviewed by the Vinante et al [31]. Zhou et al reported that the HB-EGF is involved in the transdifferentiation of the fibroblasts to adipose tissue-like cells [32]. Lee et al reported that the recombinant HB-EGF is an inhibitor of the initial commitment of differentiation of pluripotent mesenchymal stem cells to the adipogenesis [33].…”
Section: Discussionmentioning
confidence: 99%
“…We believe these pathways may be active in vivo to cause increased accumulation of adipocytes within skeletal muscle in transgenic mice overexpressing ADAM12 and resistance to a high-fat diet. Concomitantly, Zhou et al (2013) considered the role of ADAM12 in the cellular reprogramming of embryonic fibroblasts into BAT cells. Induced expression of ADAM12S (and HB-EGF) promoted lipid accumulation and an increase in expression of genes associated with BAT (PRDM16, PGC-1α, UCP-1); the expression of WAT genes was unaltered (PPARy, C/EBPα, AKT-1) suggesting ADAM12-S influences cellular plasticity of BAT but not WAT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Induced expression of ADAM12S (and HB-EGF) promoted lipid accumulation and an increase in expression of genes associated with BAT (PRDM16, PGC-1α, UCP-1); the expression of WAT genes was unaltered (PPARy, C/EBPα, AKT-1) suggesting ADAM12-S influences cellular plasticity of BAT but not WAT cells. The cellular pathways ADAM12S influences to cause reprogramming of embryonic fibroblasts into BAT cells are of interest and may be responsible for reduced interscapular BAT in ADAM12 knockout mice ( Zhou et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%